Correlation of technical difficulty during embryo transfer with rate of clinical pregnancy - Neeta Singh; Prerna Gupta; Suneeta Mittal; Neena Malhotra (Journal of Human Reproductive Sciences, 2012)
Aim: To correlate the ease or difficulty of embryo transfer and blood at catheter tip with pregnancy rate when embryo transfer (ET) was performed by the same operator using soft catheter. Materials and Methods: A retrospective analysis of 342 patients who underwent in vitro fertilization or ICSI cycle from January 2008 to December 2010 in a single centre was done. The type of transfer was divided into two groups: ′easy′ or ′difficult′. Transfer was considered difficult when additional instrumentation was required or firmer catheter was used or required changing of catheter. Patients undergoing cryo-preserved ET were excluded from the study. Results: On the day of transfer in 284 (83%) patients, ET was easy and difficulty was encountered in 58 (17%) patients. Blood at catheter was seen in 101 (29.53%) patients. In the group of 58 difficult transfers, 10 pregnancies resulted with a clinical pregnancy rate of 17.2%, while 67 pregnancies resulted in 284 cycles of easy transfer with clinical pregnancy rate of 23.6% (P value = 0.045). While no significant difference was seen in pregnancies with blood on outer catheter and blood less transfer, there was significant reduction in pregnancy rate when blood was present on catheter tip compared to bloodless transfer (13.3% v/s 24.1; P value = 0.032). Conclusion: Reduction in clinical pregnancy rate is seen with difficult ETs, more when blood is present at the catheter tip.